Energy Recovery from Brewery Waste: experimental and modelling perspectives. (March 2019) - Siqueiros, Eric; Lamidi, Rasaq O.; Pathare, Pankaj B.; Wang, Yaodong; Roskilly, A.P.
Abstract: Food and drink processing industries are extremely large consumers of thermal energy as well as bio-wastes producers. The utilisation of bio-wastes for energy recovery appears to be a good opportunity to improve the overall efficiency of process industries. In this study, waste generation, management and energy auditing of a micro-brewery located in the north east of England is investigated. Fermented grains and hops are disposed as organic wastes after the production process. Hence, this study focuses on recovery of energy from these wastes through anaerobic digestion process. Experimental work was carried out in the laboratory for the wastes characterisation. The waste samples are then anaerobically digested at 55 ⁰C and 35 ⁰C with a 5L laboratory scale continuous stirred reactor using 5 gVSL -1 and 25 days organic loading rates and hydraulic retention times respectively. Further to the experimental work, simulations were completed to evaluate the feasibility of the process. ASPEN plus simulation software was used to carry out the simulations using a novel approach for AD which is based on the ADM1 model. The experimental results showed that biogas can be produced at mesophilic and thermophilic conditions: 3.0 and 2.6 litres per day respectively. At thermophilic conditions, the methane content is 65 % while at mesophilic conditions, it is 55%. It is also found that the values of the final biogas production from the simulation were similar to the ones obtained in the experiments (-6.85%). However, the model would need further modifications to be able to accurately predict the biogas compositions. The result shows that the thermophilic process is able to fuel 126.01 kW boiler while mesophilic process can power 76.48kW boiler.